Semiotics of performing in Najwa Latif’s music videos - Sew, Jyh Wee (Pusat Pengajian Media dan Komunikasi, Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2015)
With more than 53 million hits on her YouTube videos, Najwa Latif is an icon of contemporary Malay popular culture. Just two of her music videos - Cinta Muka Buku (Facebook Love), and AdaMu (Your Existence), have received more than 12.9 million hits at the time of writing with the former earning a nomination for best Malay song at the coveted Champion Songs Award in 2011. Equally relevant is the semiotics of performing in the music videos that captures the hearts and minds of the cyberspace-inhabiting Generation Y. Contrary to the existing studies of Malay popular culture that usually focus on linguistic content we use atomization as the framework to analyze the rich and rapid visual content in Cinta Muka Buku and AdaMu. By atomizing the musical content into visual frames, we derive base units for examining the semiotic hybridity that underscores the positive identification with an online fan base. The segmented visual frames provide the locus for studying the interplay of semiotic elements in the visual symbolization. Consequently, we may identify the semiotics of performing and its relationship with the consumption of Najwa Latif’s Malay music videos in cyberspace.